Intra-professional collaboration and organization of work among teachers: How entangled institutional logics shape connectivity - Parding, Karolina; Gavin, Mihajla; Wilson, Rachel; Fitzgerald, Scott; Jakobsson, Mats; McGrath-Champ, Susan (2024)
Intra-professional collaboration is essential as it enables professionals to learn, develop, and define the terms of the profession in their own way. Yet conditions for collaboration are shaped by how work is organized and governed. This article examines how conditions for intra-professional collaboration, where work takes place with colleagues within the same profession in same or similar roles, are perceived by teachers, in relation to how work is organized, by drawing on empirical insights from a study on teachers working in education systems defined by market-driven reforms. Our findings nuance ideas of professional connectedness by showing how the organization of work, affected by ‘entangled institutional logics’ (Blomgren and Waks 2015; Alvehus and Andersson 2018) and market-based governance reforms, shapes intra-professional collaboration. Our contribution is thus to take departure from established understandings of connectivity, that is, ‘related to others and outsiders’ (Noordegraaf 2020) by examining connectivity within professions, showing how there continues to be a struggle between the profession, organization, and market which shapes conditions for intra-professional work within the teaching profession. Our analysis of intra-professional collaboration holds significance for emergent understandings of connectivity (see Adams et al. 2020a; Alvehus, Avoon and Oliver 2021: 201; Kanon and Andersson 2023) by underscoring how the contemporary organization and management of work shape the conditions that enable, or augment, inwards connectivity and the ability for professionals to collaborate in meaningful ways.